Analysis Of The Effect Of Premium Income, Underwriting Ratio, Return On Investment And Return On Equity On Profit Of Insurance Company - Hedwigis Esti Riwayati; Sendang Natalia (Management Research Studies Journal, 2022)
Abstract This study was conducted to test the effect of premium income, underwriting ratio, return on investment and return on equity on profit of insurance company.xThexmethod applied in this study was quantitative method. The population included the general insurance companies registered at Indonesia Stock Exchange in 2015-2019.xThexsamples of this study were 10 insurance companies selected using purposive sampling technique.xThextypesxof data used on this study was secondary data. The method of data collection applied was documentation method and the technique of data analysis applied was multiple linear regression with a significance level of five percent. The results of the analysis showed that: (1) premium income had positive significant effect on insurance profit, (2) underwriting ratio had positive significant effect on insurance profit, (3) return on investment had positive significant effect on insurance profit, (4) return on equity had no significant and negative effect on insurance profit.